A Report on Lead Generations Strategy - Rajpurohit, Khushi (ATLAS SkillTech University, 2024)
I completed my Summer Internship Program for a duration of 3 months at UpGrad Campus, an education technology company, that provides industry-relevant certification courses in the field of technology, data and marketing. The project named “Importance and benefits of E-learning industry ready courses and how upGrad campus helps their clients” is undertaken to understand E-learning courses in general and about upGrad campus courses and their application. Working with upGrad campus provided me with a great opportunity to learn the various aspects in Marketing and Placement Operations. I got to learn many things like working on a project to reduce marketing expenses and running a marketing campaign on an everyday basis to engage the users who visit the upGrad campus website which makes it easier for the sales team to reach out, I learned how to convince the people to buy the product which taught me how to deal with a different type of people. I also assisted in the placement where I learned what sort of course would suit which type of job profile. The study was conducted with the help of a questionnaire which was sent through Google Form. The observations from the study include how upGrad courses optimize the chances of landing a job in the domain that one is interested in by bridging the gap between the college curriculum and the industry requirements.
Project Report on A Report on Lead Generations Strategy (2022-24) Under the Guidance of Prof. Zuleika Homavazir